Spillover and crossover effects: mothers’ and fathers’ intimate partner violence, parent-child aggression risk, and child behavior problems - Pu, Doris F. (Child maltreatment, 2021)
The high co-occurrence of intimate partner violence (IPV) and physical child abuse suggests that studying these forms of aggression simultaneously, bidirectionally, and longitudinally is critical. Guided by family systems theory, this study examined parent-child aggression (PCA) risk, IPV victimization, and child behavior problems as reported by mothers and fathers when their child was 18 months and at 4 years old, to evaluate whether negative processes can transmit across family subsystems (i.e., spillover hypothesis) and/or across individuals (i.e., crossover hypothesis). Results indicated that mothers’ PCA risk predicted their subsequent IPV victimization and their reported child behavior problems (i.e., spillover effects) as well as fathers’ reported IPV victimization (i.e., crossover effect). Maternal reports of child behavior problems also predicted mothers’ reported IPV victimization and fathers’ reported child behavior problems, indicating child-driven effects. Overall, mothers rather than fathers appear more vulnerable to harmful spillover effects. Findings underscore the need for early prevention and intervention given the complex, transactional nature of family violence.